Exponential decay of eigenfunctions of Schrödinger operators on infinite metric graphs. Issue 7 (3rd July 2017) - Akduman, Setenay; Pankov, Alexander
Abstract: This paper concerns Schrödinger operators on infinite metric graphs. We show that, under natural assumptions, eigenfunctions corresponding to isolated eigenvalues of finite multiplicity decay at infinity exponentially fast.